Which Is the Best Exercise for Abductor Hallucis Activation in Hallux Valgus? A Comparison Study for New Rehabilitation Perspectives - Giacomo Farì; Laura Dell’Anna; Francesco Paolo Bianchi; Rachele Mancini; Enrica Chiaia Noya; Carlo De Serio; Riccardo Marvulli; Luisa De Palma; Danilo Donati; Roberto Tedeschi; Maurizio Ranieri; Marisa Megna; et al. (Applied Sciences)
Background: Hallux valgus (HV) is one of the most common foot deformities and negatively impacts plantar support. The abductor hallucis (AH) is the most important muscle in the etiopathogenesis of hallux valgus, but the effectiveness of its rehabilitation clashes with the difficulty of identifying the most suitable exercises to activate it. Therefore, the aim of this study was to compare four different therapeutic exercises in the activation of AH in these patients. Methods: In this observational case–control study, 48 patients suffering from hallux valgus of moderate/severe grade, according to traditional radiographic classification and the Manchester scale, were divided into two groups: the case group underwent a monthly rehabilitation protocol for their foot deformity, whereas the control group was only evaluated without any intervention. The exercises were as follows: Toe Spread Out (TSO), Short Foot (SF), Forefoot Adduction (FA), and Flexion of the Metatarsophalanges (FM). Both groups were analyzed at baseline and 1 month later (at the end of rehabilitation for the case group) while performing the four mentioned exercises using a surface electromyograph (sEMG) to record the muscle activity of AH in terms of Root Mean Square (RMS) and Maximum Voluntary Contraction (MVC). Results: FA was the only exercise to determine a statistically significant improvement in AH at the end of the rehabilitation cycle, both in terms of RMS (p = 0.015) and in terms of MVC (p < 0.0001), whereas the other exercises did not produce any change in muscle activity in the comparison between times and groups or in the related interaction. Conclusions: FA seems to be the best exercise to activate and train AH, so rehabilitation programs for patients suffering from hallux valgus should consider this exercise as the starting point for improving plantar support, always considering the specific characteristics of HV. Further studies are needed to deepen the effectiveness of this exercise, with the aim of implementing rehabilitation strategies and rethinking traditional HV therapies, which are currently predominantly surgical.